Finite element modelling of mesoscale concrete material in dynamic splitting test - Hao, Y.; Hao, Hong (Multi-Science Publishing, 2016)
Dynamic tensile strength is one of the key factors of concrete material that needs to be accurately defined in analysis of concrete structures subjected to high-rate loadings such as blast and impact. It is commonly agreed that dynamic testing results of concrete material are influenced by the inertia effect, which is very much dependent on the specimen size and loading rate. It is therefore very important to remove the inertia effect in testing data to derive the true dynamic concrete material properties. On the other hand, coarse aggregates in concrete material are usually neglected due to testing limitation or numerical simplification. It has been acknowledged that neglecting coarse aggregates might not necessarily give accurate concrete dynamic material properties. In this study, a three-dimensional mesoscale model of concrete specimen consisting of cement mortar and coarse aggregates is developed to simulate splitting tensile tests and investigate the behaviour of concrete material at high strain rate. The commercial software LS-DYNA is used to carry out the numerical simulations of dynamic splitting tensile tests. The reliability of the numerical model in simulating the dynamic splitting tensile tests is verified by comparing the numerical results with the laboratory test data from the literature. The influence of inertia effect in dynamic splitting tensile tests is investigated and removed. An empirical formula to represent the true dynamic increase factor relations obtained from dynamic splitting tensile test is proposed and verified.